RELATIONSHIPS AMONG TEST ANXIETY, LOCUS OF CONTROL AND ACADEMIC ACHIEVEMENT AMONG COLLEGE STUDENTS - Onyekuru, Bruno U.; Ibegbunam, Josephat O. (European Scientific Journal, ESJ, 2014)
This study is a correlational study designed to investigate the relationships among test anxiety, locus of control and students’ academic achievement. From a population of 498 students registered in the Department of Curriculum Studies and Educational Technology, University of Port Harcourt, Nigeria for 2009/2010 and 2010/2011 academic sessions, a sample of 364 student volunteers participated in the studies. Four research questions and three hypotheses tested at 0.05 alpha level were designed to guide the study. The instruments for data collection were College Students’ Test Anxiety Scale (CSTAS) and College Students’ Locus of Control Scale (CSLCS) validated by experts in relevant fields. Their reliability coefficients obtained through test-retest method and Pearson product moment correlation technique were 0.73 and 0.78 for CSTAS and CSLCS respectively. The data generated from these instruments were analyzed using SPSS. It was found that 28.57%, 18.13% and 53.30% of the student sample had low, high and moderate test anxiety respectively; there was a weak, but significant negative relationship between test anxiety and students’ academic achievement (r= - 0.22, p<0.05); a weak, but significant positive relationship was found between internal locus of control and students’ academic achievement (r= 0.191, p<0.05); there was a weak and insignificant negative relationship between external locus of control and students’ academic achievement (r= - 0.081, p<0.05). It was therefore recommended that students should start preparing for tests or examinations from the day a semester resumes rather than procrastinating studies until a test is at hand so as to avoid cramming and the attendant anxiety. The students must realize that hard work is a key to success and that success is determined by one’s attitude. They should purge themselves of the feeling that success in one’s life is a matter of luck.